Customer Satisfaction on Service Quality Toward Tsp Course Among Lecturers and Students in Politeknik Ungku Omar - Suryani Amin (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2019)
Unit Latihan dan Pendidikan Lanjutan (ULPL) was a unit that was responsible for managing the Time Sector Privatization (TSP) program of external courses for private agencies, industry, government agencies and public. The issue that the researcher focused in this paper was the number of participants that registered for TSP courses were decreasing by year. The paper aims to explore the role of SERQUAL in customer satisfaction among lecturers, staffs and students of UOP towards TSP courses. Convenient sampling technique was used as it helped to simplify the study based on the data received from ULPL from year 2015 until 2018 with 264 samples. Using descriptive analysis to answer the first objective regarding of the profile of the respondents. Correlation analysis to identify the relationship between the SERVQUAL dimension and customer satisfaction towards TSP courses in UOP. The results showed that customer satisfaction (dependent variable) have significance relationship with all the independent variables which are assurance, reliability, tangibility, responsiveness and empathy